2015
DOI: 10.1016/j.cmet.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2/IMP2-Deficient Mice Resist Obesity through Enhanced Translation of Ucp1 mRNA and Other mRNAs Encoding Mitochondrial Proteins

Abstract: Although variants in the IGF2BP2/IMP2 gene confer risk for Type 2 diabetes, IMP2, an RNA binding protein, is not known to regulate metabolism. Imp2−/− mice gain less lean mass after weaning and have increased lifespan. Imp2−/− mice are highly resistant to diet-induced obesity and fatty liver and display superior glucose tolerance and insulin sensitivity, increased energy expenditure and better defense of core temperature on cold exposure. Imp2−/− brown fat and Imp2−/− brown adipocytes differentiated in vitro c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
190
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 37 publications
9
190
0
Order By: Relevance
“…The upregulation of mtDNA transcripts did not reflect an increased copy number of mtDNA per cell ( Figure 3C), suggesting that HMGA2 has a direct or indirect role in regulating transcription of these genes. This functional role in mtDNA function is a novel finding not previously reported, but we note that the Igf2bp2-null mice show enhanced translation of Ucp1 mRNA and other mRNAs encoding mitochondrial proteins, which in turn is expected to affect transcription of mtDNA genes (Dai et al 2015).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The upregulation of mtDNA transcripts did not reflect an increased copy number of mtDNA per cell ( Figure 3C), suggesting that HMGA2 has a direct or indirect role in regulating transcription of these genes. This functional role in mtDNA function is a novel finding not previously reported, but we note that the Igf2bp2-null mice show enhanced translation of Ucp1 mRNA and other mRNAs encoding mitochondrial proteins, which in turn is expected to affect transcription of mtDNA genes (Dai et al 2015).…”
Section: Discussionsupporting
confidence: 68%
“…These regions varied largely in size (750,000-6,250,000 bp, median 1,500,000 bp), and contained 646 genes in total. Within the most differentiated regions we noticed several genes previously associated with size or skeletal features in other species including LCORL-NCAPG (e.g., Gudbjartsson et al 2008;Rubin et al 2012;Tetens et al 2013;Sahana et al 2015), STC2 (Gagliardi et al 2005;Rimbault et al 2013), HOXD cluster (Zakany and Duboule 2007), COL11A1 (Li et al 1995;Annunen et al 1999), and IGF2BP2 (Dai et al 2015) (Figure 4A). …”
Section: Genome-wide Scan For Signatures Of Selection In Netherland Dmentioning
confidence: 73%
See 2 more Smart Citations
“…A related member of the IMP family is IMP2 (also known as Igf2bp2), but its function is not well characterized and has only recently begun to emerge. Several studies have now identified roles for IMP2 in adult energy metabolism, obesity and type 2 diabetes (Christiansen et al, 2009;Dai et al, 2015). Additionally, studies have implicated IMP2 in the regulation of myogenesis (Li et al, 2012) and differentiation of neocortical neural precursor cells (Fujii et al, 2013).…”
Section: Introductionmentioning
confidence: 99%